(3QMeI GdCeI aj GNJdGa GdCFeIs - (3GdOeTbj GdYKeGfj GdUaOj GdTGaYj, CHh YHO Gddg, UOQ GdOjf (B- (3bGVj UaO, eMeO Hf YHO GdQMef Hf GdMSjf, J HYO (B780 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3aGf eYQaI GdELeGY hGNJdGa GdYdeGA ef Gge GdCTjGA hPdc dGRe aj Mb GdeLJgO hGdMGce dGSjeG CeI GdePGgH GdCQHY GdPjf MUd GdCNP Hbhdge aj GdeTGQb hGdeZGQH (B...s
(3BNQgG (B:s
(3hbGd GMeO dG jdRe GdhGdO ef Pdc dGHfg bGd CHh MfjaI jVefgG bjeJgG NGUI hbGd GdTGaYj jVef bjeJgG hegQgG haj VeGf bjeI GdhdO bhdGf hbG CMeO dG jdReg bjeJgG (B... (3hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/193s
(3cTa GdXfhf (B1/836s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdTGaYjs